Pojęcie przestępstwa lingwistycznego i jego typologie - Falana-Jafra, Anna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The aim of the article is to formulate a definition of linguistic crimes as a specific type of crimes penalised in Polish criminal laws and to categorise them according to the following criteria: the nature of the perpetrator’s enforcement activities; the use of language or failure to use it; the length of the linguistic enforcement activities; the authorship of statements; the nature of the legal good to be protected. Human behaviour, which is legally classified as a linguistic offence, is performative in nature and therefore has the legal effect of making the offender criminally responsible and of imposing criminal sanctions on him/her by the competent state authorities. In the article, the performative function of language will be extended to include the notion of passive performativity, resulting from an offence committed as a result of the failure to use language in situations where its use is required by the legal system.